Lithium-isotope fractionation during continental weathering processes - Pistiner, J; Henderson, G (2003)
A comprehensive understanding of lithium-isotope fractionation during terrestrial weathering is necessary in order to use lithium isotopes to trace chemical cycles, climatic changes and igneous processes. This study investigates lithium-isotope fractionation in two laboratory experiments and by analyses of natural basalt weathering products. Partial dissolution of basalts in the laboratory does not result in fractionation of lithium isotopes but similar dissolution of a granite sample causes significant fractionation. This may reflect dissolution of secondary minerals from the granite, or differences in the Li-isotope composition of primary minerals in this more evolved igneous rock. Significant Li-isotope fractionation was also observed during sorption onto mineral surfaces in the laboratory, although this was highly dependent on sample mineralogy. No fractionation accompanies the outer-sphere physisorption of Li to smectite surfaces. Some fractionation accompanies sorption onto ferrihydrite and significant fractionation with α=0.986 is seen during inner-sphere chemisorption to gibbsite surfaces. Repeat experiments with varying amounts of sorption demonstrate that Li remains in an exchangeable site on the gibbsite surface. The extent of fractionation onto gibbsite observed in this study (∼13‰) is about half that required in order for clay-surface removal to balance the ocean Li-isotope budget. Isotopic fractionation of Li was found to occur on a <300-yr timescale in both cold and warm natural environments. A minimally altered rock surface from Iceland was found to be two lighter in δ7Li than the sample interior, probably due to the preferential incorporation of 6Li in clay or oxide-rich alteration products on the sample surface. Soil samples from Hawaii also demonstrate Li fractionation during weathering. In this environment, rainwater (δ7Li=10) contributes a significant flux of isotopically heavy Li to the developing soil. Despite this, soils have similar Li-isotope compositions to the primary basalt (δ7Li=4), indicating that 6Li is preferentially retained during weathering. This conclusion is supported by isotopically heavy river water on Hawaii (δ7Li=22) and by the correlation between Li concentration and δ7Li in the soil. The lab- and field-based measurements of this study clearly demonstrate that lithium fractionates during weathering, potentially providing information about the weathering environment now and in the past. © 2003 Elsevier B.V. All rights reserved.